PERANCANGAN BASIS DATA PENJUALAN PADA KONVEKSI RAFKA BABY - Erambono, Hiu Hawaririn; Nurul Ilmi, Ajeng Hilmi; Fikri, Agung Muhamad; Hismanudin, Fiqih; Lamadorok, Marianus Ara Goran; Masan, Paskalis Beda; Nurjanah, Sri Putri; Salshabila, Vini Shiva; Firmansyah, Ricky (Pusat Riset dan Inovasi Nasional, 2022)
Rafka Baby Convection is an industrial business that produces baby clothes that has been established since 22 years ago. Sales data collection at the Rafka Baby Convection is still done manually. This study aims to find out what are the needs and problems in sales data collection and to design a sales database in developing the Rafka Baby Convection business. The method used in this study is the method of data collection by interview and literature study, as well as the system design method, which means the author designs a new database system based on the results of data collection. The results show that sales at Rafka Baby Convection are still manual in the sense that sales are made without a database system regarding the goods sold, buyers, payments, and transactions. Therefore, a database design was made to help collect data on the Rafka Baby Convection. The database created is designed using a MySQL database and is managed in the PhpMyAdmin application. This database design is expected to be able to provide convenience in collecting sales data at Rafka Baby Convection.